Disturbances in the ploidy level in the gynogenetic sterlet Acipenser ruthenus - Fopp-Bayat, D. (J Appl Genet, 2017)
Artificial mitotic gynogenesis, a chromosome set manipulation, is applied to provide the homozygous progeny with only maternal inheritance. Here, gynogenetic development was induced in the sterlet Acipenser ruthenus L. (Acipenseridae) by activation of the eggs originating from albino females with the UV-irradiated spermatozoa from wild-coloured males, followed by the heat shock applied to suppress the first mitotic division in the haploid zygotes. All experimentally obtained gynogenetic offspring possessed recessive albino coloration. Moreover, the genetic verification, based on three microsatellite DNA markers, confirmed the only maternal inheritance in the albino progeny. Cytogenetic screening enabled identification of the aneuploids, haploids, diploids, triploids, tetraploids and mosaic individuals among the gynogenetic larvae that hatched from the eggs subjected to the heat shock. Furthermore, 40% of the larvae from the haploid variants of the research that were not exposed to the temperature shock showed the diploid chromosome number. A variation of the ploidy level observed in the gynogenetic sterlets may be the consequence of the spontaneous polyploidisation that occurred in the haploid zygotes. Moreover, observation during embryogenesis showed varied stages of eggs development and the asynchronous cell cleavages that may have resulted in the chromosomal disturbances observed in the gynogenetic sterlets here.